Five Language Style In The Sea Speaks His Name Novel Leila S. Chudori - Rifani Andrian Putri; Hidayati Hidayati; Misla Geubrina (Jurnal Pendidikan dan Sastra Inggris, 2023)
Language style is a formal form of language that is used to communicate with others. The purpose of this research is to examine the language employed style used in the novel The Sea Speaks His Name. This Novel is a historical fiction authored by Leila S. Chudori and released in Jakarta in 2017. The data is taken from the novel The Sea Speaks His Name conversation text. A qualitative descriptive research design was used in this study. This analysis is based on Martin Joos' (1976) concept of five language style : frozen styles, formal styles, consultative styles, casual styles, and intimate styles. The results indicate there are thirty (30) data points from the film's conversations to conduct figurative language. The data analyzed shows that the novel has twenty-four cases of frozen (none), formal (one), consultative (seven cases), casual (eleven cases), and intimate (five cases) styles.. This means that the most common casual style is obviously used in family and close friend communication. Based on the findings of the study, students in the English Department should conduct additional analysis of the five language types employed in other materials such as films, books, or articles.